NEMO-PISCES DSi concentration in the Labrador Sea ... - Alizee Dale; Ethe, Christian; Alekseenko, Elena; Gehlen, Marion (ESPRI/IPSL, 2023)
This focus on the Labrador Sea is part of the global NEMO-PISCES model used in the publication "Contribution of physical processes to dissolved silica variability in the Labrador Sea between 1980-2015" by Dale et al., to be submitted in Geophysical Research Letters. The variables provided are as follows: dissolved silica (Grid_T), conservative temperature (Grid_T), absolute Salinity (Grid_T), mixed layer depth (Grid_T), specificity of the grid (mesh_mask), effective transport (Grid_U and Grid_V). The associated paper investigates the drivers of the decline in the pre-bloom Dissolved Silica (DSi) inventory observed in the upper layer (0-450 m) of the Labrador Sea between 1994-2007 and its InterAnnual Variability (IAV) over the 1980-2015 period. It assesses the relative contributions of the variability of deep winter convection (DWC) and inflow from the Arctic as DSi sources using an eddy-permitting biogeochemical ocean general circulation model. The IAV of the upper layer DSi inventory co-varies with both the ...